DESAIN E-MICROTEACHING SEBAGAI APLIKASI E-LEARNING PADA LEMBAGA PENDIDIKAN TINGGI KEGURUAN - Febrino, Febrino (Tarbawy : Jurnal Pendidikan Islam, 2022)
The development of e-Microteaching applications is motivated by the demands for innovation due to education disruption. Teacher Universities are required to use LMS-based e-learning in lectures to improve the quality of education. In the implementation of Microteaching lectures, it is necessary to pay attention to the e-learning facilities to ensure the quality of training for prospective teachers. Many research results show that Open Source LMS is effectively used in lectures, but there are still few lecturers who can develop it. Selection of Proprietary LMS can be a solution to be developed. For this reason, the purpose of this research is to obtain a valid e-Microteaching application design. This development research adapts the steps of the Plomp (2013) model. The stages of development are preliminary research, prototyping phase. In the preliminary research, a preliminary study is conducted by conducting a needs analysis, literature review and framework development. The prototyping phase consists of three stages, namely: designing the prototype, conducting formative evaluation and revising the prototype. Formative evaluation was conducted to determine the validity of the prototype of the e-Microteaching application model and the application manual. The results showed that the e-Learning application model based on the Proprietary Learning Management System in Microteaching lectures at PTKIN which was developed in the form of an e-Microteaching application and manual for its use, had met the criteria of a valid model. The validation results from the experts show that the e-Microteaching application and user manual are very valid from the aspect of content, construction and language.